The theory of mind construct in adulthood: perspective taking in relation to language and executive function - Montgomery, Derek E.; Tompkins, Virginia; Feng, Xin (Frontiers in Psychology, 2024)
There are conflicting proposals about the underlying structure of the theory of mind (ToM) construct. The lack of clarity impedes attempts to understand relationships between ToM and other cognitive abilities. This study investigated the nature of the ToM construct and its relation to cognitive variables by administering a battery of ToM measurements along with measurements of executive function and general vocabulary to 207 (Mage = 19.26) adult participants. Associations between ToM tasks were statistically significant after controlling for covariates, but, for the most part, very weak in magnitude. The strongest relationship was between the Strange Stories and Higher-Order False Belief measurements. Previous theoretical analysis proposes those instruments are conceptually linked by a perspective taking requirement that entails representing another's mental state. Results from a factor analysis suggested an underlying ToM structure-a protagonist perspective factor. The Strange Stories, Higher-Order False Belief, and Frith-Happé Animation tasks loaded onto the factor. Its defining feature is the ascription of mental states to predict and explain protagonists' actions that take place within a narrative structure. It is related more strongly to vocabulary than executive function and it provides grounds for future research on the role of narrative processing in ToM reasoning.